Endoscopy-assisted sentinel lymph node biopsy and mastectomy in breast cancer: initial experience at a Peruvian oncological institution - Torres-Maldonado, Jorge (2025)
Endoscopic surgery has enabled performing multiple types of minimally invasive surgical approaches, including breast surgery. This technique is commonly used in Asian countries. Surgical options include single-port nipple and skin sparing surgery, which is reported to be oncologically safe and well tolerated. We present the first report in Peru on this surgical procedure in a patient with breast cancer treated with neoadjuvanttherapy, where we describe the surgical technique and the anatomopathological and aesthetic results.